MANAGEMENT OF LITERACY CULTURE AT PAUD OF ISLAMIC BABY SCHOOL ELMAFAZA - Elly Damaiwati; Abdul Basid Adnan (Pondok Pesantren Modern Islam Assalaam, 2023)
This research aims at determining the process of management of literacy culture development at Early Childhood Education (PAUD) of Islamic Baby School Elmafaza. This research was qualitative conducted at Early Childhood Education of Islamic Baby School Elmafaza. Technique of collecting data applied observation, interview and documentation. Technique of data validity used triangulation. Technique of data analysis applied interactive analysis model encompassing data reduction, data display and conclusion.The results of this research conclude that the management of literacy culture at PAUD of Elmafaza is divided into three stages, starting from the planning stage which includes setting a large vision related to literacy. Then, it is followed by lowering the vision and mission of the institution into the school curriculum. The implementation phase includes: a) parents’ socialization, b) Reading Habits is getting used to 10 minutes for reading at school, c). strengthen the role and the function of the school library and book corner in each class, d). Book corner program at home, e). Home visit. It is the hospitality of Elmafaza teachers to the house to see the book corner at home and the programs that have been implemented, f) Organizing Seminars and Talk Show related to Literacy Culture, g). Literacy for children with special needs: stimulates reading to children with special needs, h). There is a teacher writing program that encourages and facilitates teacher writing i) joining Gernas Baku activities and, j) holding some literacy competitions, i.e., writing and telling stories. The evaluation phase includes supervision conducted by the school and sees the results of this literacy culture for children and the school environment. This literacy culture fosters eagerness or love of reading in students. This love of reading is very important because it becomes the basis for the development of one’s learning motivation.Learning motivation is the key to success in life.